On Lessons Learned From Distance Teaching and Learning - Entina, Sofya (Computer Tools in Education, 2021)
The coronavirus (COVID-19) epidemic in Russia forced colleges and universities to switch to distance teaching and learning. The instructors had to make an emergency move to the remote methods of teaching using various platforms. In the course of the distance learning period in midst of an on-going pandemic, the instructors acquired valuable experience in on-line lecturing, administering  tests, conducting tutorials, examination sessions, office hours, etc. Distance teaching called for new educational technologies that would provide the quality of education comparable to the in-person teaching. Compared to the traditionalteaching, the time needed to prepare for classes has increased. However, it turned out that thanks to the technologies developed to facilitate high-quality distance interaction, many of the methodologies developed for distance learning can be quite useful in traditional (in-person) learning as well. Using a course in Linear Algebra and Algebraic Structures taught to the freshmen at Saint Petersburg Electro-technical University as an example, this article demonstrates that it is possible to use some of the communication technologies–based methodologies to enhance in-person learning.
Keywords: distance teaching, traditional teaching, in-person teaching, distance education technologies, communication technologies